THE STUDENTS’ PERCEPTION TOWARDS PEER FEEDBACK AS SOCIAL-AFFECTIVE STRATEGY IN WRITING RECOUNT TEXT SKILL - Karisma Kurniawati (Journal of English Educational Study (JEES), 2022)
Writing becomes a tricky skill to learn by the students since it has complex processes. As a result, many students have difficulties and problems while writing. To overcome the problems in writing due to its complexities, the students need to use learning strategies. One of the learning strategies in writing is peer feedback as a social-affective strategy. Therefore, this study aims to describe how the students’ perception of peer feedback as a social-affective strategy in writing a recount text. This study used descriptive qualitative research as the research design. The researcher used an open-ended questionnaire and semi-structured interviews as the instruments to collect the data. Furthermore, this study involved 21 students at one of the senior high schools in Gresik selected by using purposive sampling. The results of this study showed that based on the students’ perception, peer feedback as the social-affective strategy was effective, important, and brought many benefits for the students in increasing their ability to write recount text. However, there were also some disadvantages of peer feedback along with the students-provided solutions. Thus, the educators and teachers were recommended to consider and apply peer feedback as a social-affective strategy in the writing class since it is very useful and affects the students' writing abilities.